Determinantes sociobiológicos da insegurança alimentar em residências com crianças menores de cinco anos: pesquisa nacional de demografia e saúde da criança e da mulher (PNDS - 2006/07) - Fonseca, Ana Paula Poblacion da [UNIFESP] (2016)
Food Security is the right to regular and permanent access to nutritionally adequate food in sufficient quantity, without compromising access to other essential needs, based on food practices that promote health. The Brazilian Food Insecurity Scale (EBIA) is a psychometric scale that directly measures food insecurity at the household level, classifying it as mild, moderate or severe. The National Survey on Demography and Health of Women and Children (PNDS-2006/07) was a national household survey, which together with indicators and measurement instruments in various areas, described Food Security prevalence. PNDS-2006/07 secondary data was used to analyze the association between food insecurity and sociodemographic and biological variables among Brazilian households with children under five years of age.The food security variable was dichotomized as food security or mild food insecurity (SA/IAL) versus moderate or severe food insecurity (IAM/G), and the first paper results showed high prevalence of SA/IAL concentrated in the North (N) or Northeast (NE) (30.7%), in economic classes D or E (34%), and beneficiaries of Cash Transfer Programs (PTR) (36.5%). The multivariate analysis model found that social risks (beneficiary PTR), regional risks (N/NE) and economic risks (classes D or E) were 1.8, 2.0 and 2.4, respectively. By aggregating the three risks we found 48% of households in SA/IAL, meaning that adult and children experienced hunger during the three months period preceding the survey. Second paper describes high prevalence of IAM/G (Food Insecurity) in households where mothers had fewer than 8 years of education (25.7%), lived without a partner (25.9%), or had three or more children living under the same roof (29.3%). In addition, it showed high prevalence of Food Insecurity in households with children under five, who have had at least one episode of diarrhea or pneumonia during the three months prior to interview (25.9%), had weight-for-age <-2.0Z (32.1%), or had not eaten meat (20.5%) or fruits and vegetables every day in the past seven days before interview (19.3%). Independently of geographic location (macro-region and urban-rural classification) and household variables (economic status, cash transfer program, living conditions, maternal education, marital status and number of children), the multivariate analysis model showed association between health of children living in food-insecure households and having had at least one hospitalization for diarrhea or pneumonia within the twelve months before the interview (aPR 1.3; 95%CI 1.1; 1.6), underweight shown by weight-for-age WAZ<-2.0Z (aPR 1.4, 95%CI 1.1; 1.7), and having not eaten meat (aPR 1.2, 95%CI 1.1; 1.4) or fruits & vegetables every day in the past seven days prior to interview (aPR 1.7, 95%CI 1.3; 2.3). There is a relationship between living in moderate or severe food insecurity and objective adverse child health outcomes. These relationships are shaped by the environment where the child is inserted, and may represent an important factor in the transmission of socioeconomic inequality across generations, impacting negatively on the prosperity of future Brazilian citizens.